Advanced practice role delineation within Hong Kong: A cross‐sectional study. (8th July 2022) - Jokiniemi, Krista; Chair, Sek Ying; Wong, Frances Kam Yuet; Bryant‐Lukosius, Denise
Abstract: A career ladder for nurses, including several levels of nursing practice and specific roles for advanced practice nurses, was introduced in Hong Kong around the start of the 21st century. To date no studies have distinguished the practices of advanced practice nurses in Hong Kong. This cross‐sectional study, conducted between November 2020 and March 2021, aims to identify and differentiate the practice patterns of advanced practice nurses by utilizing the Advanced Practice Role Delineation tool. A total of 191 responses were obtained. Three roles were identified: nurse consultant, advanced practice nurse, and advanced practice nurse in management. Among the five advanced practice nursing domains, nurses were most frequently involved in Education and in Direct Comprehensive Care activities, while least active in Research and in Publication and Professional Leadership. Identifying activities in various nursing roles helps to differentiate their responsibilities and provides new insights for role utilization and support. Although the role characteristics are shaped by country contexts, research evidence on practice patterns may be used to support international discussion and efforts to promote role clarity and effective role introduction and optimization.